Demographic Change and New Zealand's Economic Growth - John Bryant (New Zealand Government, The Treasury, 2003)
New Zealand has, by OECD standards, high birth rates. This has provided New Zealand with a relatively young population and continuing labour force growth. Both these features are, on many accounts, good for economic growth. Yet most discussions of New Zealand's economic performance and its prospects for moving up the OECD income distribution have paid little attention to demography. This paper defines "demography" narrowly as population size, growth, and age-structure, and examines the likely effects on New Zealand's growth rate in GDP per capita, relative to the rest of the OECD. The first part of the paper gives a broad overview of trends in population size and age structure in New Zealand and elsewhere in the OECD. The second part describes selected demographic trends in more detail and discusses their economic significance. The overall conclusion is future demographic trends are likely to provide New Zealand with a small advantage, relative to the rest of the OECD.
Keywords: J1; 330; New Zealand; OECD; demography; economic growth